Climate change induced flash floods in federal capital territory, Abuja, Nigeria: Media shaping awareness? - Omoera, Osakue Stevenson; Guanah, Jammy Seigha (Przegląd Krytyczny, 2022)
Devastating flash floods and uncontrollable soil erosion, largely fallout of the effects of climate change, have been taking their toll on Nigeria’s Federal Capital Territory (FCT), Abuja. Apart from disrupting the ecosystem, their overwhelming effects are felt in the agricultural sector as farmlands are washed away. The media are expected to enlighten the residents of FCT, Abuja, about the impact of climate change. They have to be aware of global warming and its effects. Hence, this article sought to determine the level of awareness about the existence of climate change discourse among the residents of the FCT, Abuja; to ascertain respondents’ perception about the media creating enough awareness around climate change and how it exacerbates flooding, and to confirm if the press is mobilising residents enough on how to mitigate flooding. The study was anchored on Status Conferral and Media Development theories. A questionnaire and question guide served as instruments for data collection. Findings showed that the FCT residents’ awareness level about climate change was generally low, whereas improvement on the awareness level will result in activities that reduce flash floods; they perceived the media as not creating adequate awareness about climate change and educating the populace enough on how to mitigate the flash flood problem. In their sensitisation exercises, the media should partner with relevant government agencies and traditional rulers to educate residents on safety issues, particularly human activities that tend to exacerbate flash floods in the area.